Utilization of Youtube to Increase Student Appreciation Against Archipelago Dance in the Subject of Basic Concepts of Dance Art PGSD Study Program FKIP Bengkulu University - Anggraini, Dwi; Hasnawati, Hasnawati (Universitas Nusantara PGRI Kediri, 2019)
This study aims to increase students' appreciation of the archipelago dance by utilizing youtube in learning Basic Concepts of Dance for VA semester students PGSD Study Program FKIP Bengkulu University. The research method used is action research conducted in two cycles. The data collection technique is observed using an appreciation observation sheet instrument. Data analysis using percentage analysis. In the first cycle, the observations of student appreciation of the archipelago dance in the observation step were 33.3% in the sufficient category and 66.7% in the good category, appreciation 66.7% in the sufficient category and 33.3% in the good category , appraisal / award 50% is insufficient category and 50% in good category, and empathy 66.7% is in the adequate category and 33.3% is in the good category. In the second cycle, the observations of student appreciation of the archipelago dance at the 50% observation step are in a good category and 50% are in the very good category, appreciation 33.3% is in a good category and 66.7% is in the very good category, assessment/award 16.7% were in good humor and 83.3% in the very good category, and empathy 33.3% were in the good category and 66.7% were in the very good category. Based on these data, it can be seen that the appreciation of students for archipelago dance by using youtube in learning the Basic Concepts of Dance is increasing.